2022
DOI: 10.1128/spectrum.02100-21
|View full text |Cite
|
Sign up to set email alerts
|

High Mycobacterium tuberculosis Bacillary Loads Detected by Tuberculosis Molecular Bacterial Load Assay in Patient Stool: a Potential Alternative for Nonsputum Diagnosis and Treatment Response Monitoring of Tuberculosis

Abstract: This paper highlights the value of stool as a sample type for diagnosis of tuberculosis. While other studies have used DNA-based assays like the Xpert MTB/RIF and culture to detect Mycobacterium tuberculosis in stool, this is the first study that has applied TB-MBLA, an RNA-based assay, to quantify TB bacteria in stool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…The need for an alternative sample type to diagnose TB cannot be more strongly emphasized. We have shown that viable M. tuberculosis bacilli are quantifiable by the TB molecular bacterial load assay (TB-MBLA) in stool samples processed using OMNIgene-Sputum (OM-S) medium ( 4 ).…”
Section: Lettermentioning
confidence: 99%
See 2 more Smart Citations
“…The need for an alternative sample type to diagnose TB cannot be more strongly emphasized. We have shown that viable M. tuberculosis bacilli are quantifiable by the TB molecular bacterial load assay (TB-MBLA) in stool samples processed using OMNIgene-Sputum (OM-S) medium ( 4 ).…”
Section: Lettermentioning
confidence: 99%
“…A set of stool samples corresponding to those processed in the OM-S study were processed using PBS and stored at −20°C until RNA extraction was performed ( 4 ). Six grams of stool per patient was processed within 20 min after collection, prior to storage.…”
Section: Lettermentioning
confidence: 99%
See 1 more Smart Citation
“…DNA-based Xpert MTB/RIF assays are very sensitive, but their positivity does not necessarily mean viable TB bacilli [ 4 , 5 ]. Recent reports demonstrate the promising performance of the Xpert MTB/RIF Ultra in pediatric stools and cerebrospinal fluid [ 6 ], which will improve the detection of TB in this group of patients and those who cannot produce sputum.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports have demonstrated that the Tuberculosis Molecular Bacterial Load Assay (TB-MBLA) VitalBacteria ™ has potential to replace culture on monitoring bacterial load during TB treatment (7)(8)(9). The 2018 global tuberculosis report acknowledged TB-MBLA as a candidate to replace smear microscopy and culture for monitoring treatment response (10).…”
Section: Introductionmentioning
confidence: 99%